Perception Ease of Use and Fintech Adoption: The Mediating Role of Trust and the Moderating Role of Security - Agustin, Restiana; Anjani, Tiya Melida; Khairunnisa, Jihan; Haya, Aqila Fadia (Growth: Journal Management and Business, 2025)
This study examines how perceived ease of use contributes to the intention to use Financial Technology services, considering trust as a mediating variable and security as a moderating variable. The aim of this research is to analyze the influence of perceived ease of use on the intention to use Financial Technology, with trust as a mediator and security as a moderator. The method employed is quantitative, using a survey approach by distributing questionnaires to 89 respondents, the majority of whom are students aged 18–24. The analysis was conducted using Partial Least Squares (PLS). The results indicate that perceived ease of use contributes to the intention to use financial technology and positively influences trust. However, trust does not contribute to the intention to use and does not mediate the relationship between perceived ease of use and the intention to use financial technology. Furthermore, security does not moderate the relationship between perceived ease of use and trust. These findings suggest that ease of use is more dominant in influencing the intention to use financial technology compared to trust and security. Theoretically, this study refines the Technology Acceptance Model (TAM) by affirming the primacy of perceived ease of use while revealing that trust and security play a diminished role among younger users. This finding underscores the contextual nature of TAM, suggesting that usability factors may outweigh relational and safety considerations in shaping financial technology adoption. The practical implication is that financial technology service providers should prioritize ease of access and user experience. The limitation of this study lies in the homogeneity of the respondents' demographics; therefore, further research with a broader scope is recommended to obtain a more representative understanding.